Developing a Neurocare Framework for Migraine Management - Priya R L; Gresha Bhatia; Dr. Bindu Menon; Tanvi Naik; Sanika Hadap; Ajay Iyer; Arya Banavali (International Journal of Medical Toxicology and Legal Medicine, 2024)
Migraine, a neurological disorder impacting over one billion people worldwide, leads to debilitating headaches and diminished quality of life. Existing mobile applications and machine learning (ML) models offer some support for migraine management but often lack comprehensive care, real-time insights, and essential assessment tools like the MIDAS questionnaire. Current solutions are also limited in tracking triggers and capturing complete patient histories, highlighting the need for a more holistic approach. This review evaluates 20 migraine-focused applications(14 mobile and 6 web-based) and 13 ML/deep learning (DL) studies, identifying key limitations and paving the way for improved solutions. In response, NeuroCare, a prototype app, provides validated MIDAS assessments, personalized tracking for symptoms and triggers, detailed migraine logs, and electronic health record (EHR) displays for healthcare providers. This study demonstrates NeuroCare’s potential as a comprehensive tool with future AI/ML integrations, benefiting both patients and clinicians in effectively managing migraines.